THE DETERMINANTS OF FDI FLOWS IN OIC COUNTRIES - Heri Sudarsono (Universitas Islam Indonesia, 2008)
The objective of this study is to identify the determinants of foreign direct invest-ment (FDI) in OIC countries. In order to undertake it, we perform an econometric model based on panel data analysis for OIC countries, consisting of 16 Asian OIC countries and 18 African OIC for the 1980-2000 periods. Some estimated coefficients have the expected signs and are statically significant, such as market size and openness. The estimated negative sign on the variables exchange rate capturers the effect alters the price for acquiring assets in the OIC countries. In this case of OIC countries exchange rate also depict that the exchange rate regime is by no mean neutral to FDI. Furthermore, the variables consumption prices index (CPI) positive by effect FDI for African and all OIC countries. The government consumption of OIC countries was not significant suggesting that such factor does not play a role in at-tracting foreign investment. Finally, the more open economies in OIC countries were more attractive to foreign capital flows, as expected.Keyword: FDI, OIC, openness, panel data